Automatic computation of bending sequences for wire bending machines. Issue 12 (2nd December 2022) - Baraldo, Andrea; Bascetta, Luca; Caprotti, Fabrizio; Chourasiya, Sumit; Ferretti, Gianni; Ponti, Angelo; Sakcak, Basak
ABSTRACT: Determining a feasible bending sequence, i.e., ensuring absence of wire self-collisions and wire-machine collisions, or even an optimal bending sequence, i.e., minimising time or energy required to perform it, is a difficult and time-consuming task for complex workpieces, even for expert operators. Introducting algorithms for the computation of wire-bending sequences is thus crucial to increase productivity and production flexibility, and to decrease production costs. This work proposes an algorithm to automatically determine an appropriate bending sequence for a given workpiece, bending tool, and machine 3D CAD model, which leverages on a representation of the wire as a robotic manipulator and of a bending sequence as a tree, and on the adoption of A* as graph search algorithm. A cost and a heuristic function, suitable for the wire-bending problem, and an approach to parallelise the execution of A* are introduced, as well. In this way, a computationally simple and efficient wire-bending sequence computation algorithm is devised, able to determine a solution in an amount of time less or equal to the time used by an expert operator, without the need of high computational power. The effectiveness of this algorithm is assessed on two different test cases, relevant to industrial workpieces.